Augmented Intelligence for National Security and Development - Suman, Sristi (Unity Journal, 2022)
Augmented Intelligence is a system model which centre on the partnership between human general intelligence & common sense with Artificial Intelligence’s exceptional processing speed and computation power to get better cognitive performance. This study can shed light on Augmented Intelligence and how it can be implemented so that we have heroes working at the peak human level possible, suffer fewer casualties, and also have equal footing in terms of technology and military strength. Nepal being open bordered country has a great threat from the border issues and with ever-rising crime and challenges in various cities creating intra threat. The study analyses to overcome this geographical challenge, operational problems, the rise of conflicts, and establish better policies, faced by security personnel with technology that actually empowers all the brave soldiers and Police officers to maintain security from both external and internal risk. In the ever-evolving technology limitations of human beings can be catastrophic, but replacing it all with Artificial Intelligence is not a practical solution as well because it would be giving the third entity all the ability that might revolt against humans themselves. The article can be summed up as, research on the practicality of Artificial Intelligence and Augmented Intelligence in national security and figure out a way for its legal adaptation. The availability of various case studies, surveys, research on various existing technology, and research papers published in renowned journals and publications has made this study possible.